Analysis of Determining the Cost of Goods and Applying the Cost PlusPricing Method in Order to Determine the Selling Price at The Soto Abbas Madura Restaurant, Sidoarjo Branch - Zahroh, Fathimatus; Safvitri, Cindy; Syahruddin, Ahmad Dhani; Adiyanto, Mochamad Reza (ProBisnis : Jurnal Manajemen, 2023)
Production costs are one part of determining the cost of products from RMSAM. Rumah Makan Soto Abbas Madura as well as knowing the determination of the price of RMSAM and can determine how much return on capital that has been issued so as to generate profits.RMSAM also as a business that makes food is also inseparable from the problem of achieving profit, and return on capital. The method used is a descriptive method using a qualitative approach can also use research for the calculation of the cost of goods produced and the collection of costs that have been incurred for the food business. For Return on Capital RMSAM business with the resulting production capacity. interview shows that RMSAM, experiencing stable financial conditions can even achieve maximum results. The costs that have been incurred should be used as an element of the calculation of the formation of the cost of goods produced and the determination of the selling price. RMSAM leaders should maintain and improve the business as well as possible and innovate if they want the business to survive as an advanced restaurant in the Madura area.